2018
DOI: 10.1111/1365-2656.12928
|View full text |Cite
|
Sign up to set email alerts
|

The importance and adaptive value of life‐history evolution for metapopulation dynamics

Abstract: The spatial configuration and size of patches influence metapopulation dynamics by altering colonisation–extinction dynamics and local density dependency. This spatial forcing as determined by the metapopulation typology then imposes strong selection pressures on life‐history traits, which will in turn feed back on the ecological metapopulation dynamics. Given the relevance of metapopulation persistence for biological conservation, and the potential rescuing role of evolution, a firm understanding of the relev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This experiment confirmed the antiphase oscillations predicted from theory when prey evolves defence strategies. While such prominent examples of the integration of theory and empirical data on EEFs exist (see among others also, Becks et al., ; Bonte & Bafort, ; De Meester et al., ; Fischer et al., ; Fronhofer & Altermatt, ; Huang et al., ; Litchman, Klausmeier, & Yoshiyama, ; Metcalf et al., ; Thomas, Kremer, Klausmeier, & Litchman, ; Van Nuland, Ware, Bailey, & Schweitzer, ) breadth of the theoretical work highlighted here, the coupling of empirical data from natural and experimental settings, with theoretical models, needs to be deepened. This gap between theory and empirical work may, in part, be due to differences in technical jargon that impede effective communication between theoreticians and empiricists as well as modelling specializations among theoreticians which impede synthesis or at least slowdown progress.…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…This experiment confirmed the antiphase oscillations predicted from theory when prey evolves defence strategies. While such prominent examples of the integration of theory and empirical data on EEFs exist (see among others also, Becks et al., ; Bonte & Bafort, ; De Meester et al., ; Fischer et al., ; Fronhofer & Altermatt, ; Huang et al., ; Litchman, Klausmeier, & Yoshiyama, ; Metcalf et al., ; Thomas, Kremer, Klausmeier, & Litchman, ; Van Nuland, Ware, Bailey, & Schweitzer, ) breadth of the theoretical work highlighted here, the coupling of empirical data from natural and experimental settings, with theoretical models, needs to be deepened. This gap between theory and empirical work may, in part, be due to differences in technical jargon that impede effective communication between theoreticians and empiricists as well as modelling specializations among theoreticians which impede synthesis or at least slowdown progress.…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Changes in fluxes among patches are known to directly impact metapopulation and local population dynamics (Cheptou et al , ; Bonte et al , ). These demographic changes result from direct changes in the spatial structure of the network, for instance by changes in connectedness, patch size or the presence of external extinctions or from trait evolution (De Roissart et al , ; Bonte & Bafort, ). Moreover, spatial networks are usually heterogeneous and modular with respect to their topology (Fahrig, ; Urban & Skelly, ; Ferrari et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Our review revealed an array of methods for estimating connectivity, including telemetry, movement ecology modeling, and gene flow estimation. Modeling approaches included systems modeling and dispersal kernels (Bonte & Bafort, 2019;Summers et al, 2012). Gene flow estimates are well established in the literature for understanding connectivity, and were measured through landscape genetics approaches, which have been applied to other conservation questions, such as restoration (Kaus et al, 2019;Manel et al, 2003;Proft et al, 2018).…”
Section: Connectivitymentioning
confidence: 99%